Delineation of motoneuron subgroups supplying individual eye muscles in the human oculomotor nucleus - Che-Ngwa, Emmanuel; Zeeh, Christina; Messoudi, Ahmed; Büttner-Ennever, Jean A.; Horn, Anja K. (Frontiers in Neuroanatomy, 2014)
The oculomotor nucleus (nIII) contains the motoneurons of medial, inferior and superior recti (MR, IR, SR), inferior oblique (IO) and levator palpebrae (LP) muscles. The delineation of motoneuron subgroups for each muscle is well-known in monkey, but not in human. We studied the transmitter inputs to human nIII and the trochlear nucleus (nIV), which innervates the superior oblique muscle (SO), to outline individual motoneuron subgroups. Parallel series of sections from human brainstems were immunostained for different markers: acetylcholine transferase (ChAT) combined with glutamate decarboxylase (GAD), calretinin (CR) or glycine receptor (GlyR). The cytoarchitecture was visualized with Cresyl violet, Gallyas staining and expression of non-phosphorylated neurofilaments (NP-NF). Apart from nIV, seven subgroups were delineated in nIII: the central caudal nucleus (CCN), a dorsolateral (DL), dorsomedial (DM), central (CEN), and ventral group (VEN), the nucleus of Perlia (NP) and the non-preganglionic centrally projecting Edinger-Westphal nucleus (EWcp). DL, VEN, NP and EWcp were characterized by a strong supply of GAD-positive terminals, in contrast to DM, CEN and nIV. CR-positive terminals and fibres were confined to CCN, CEN and NP. Based on location and histochemistry of the motoneuron subgroups in monkey, CEN is considered as the SR and IO motoneurons, DL and VEN as the B- and A-group of MR motoneurons, respectively, and DM as IR motoneurons. A good correlation between monkey and man is seen for the CR input, which labels only motoneurons of eye muscles participating in upgaze (SR, IO and LP). The CCN contained LP motoneurons, and nIV those of SO. This study provides a map of the individual subgroups of motoneurons in human nIII for the first time, and suggests that NP may contain upgaze motoneurons. Surprisingly, a strong GABAergic input to human MR motoneurons was discovered, which is not seen in monkey and may indicate a functional oculomotor specialization.